Senior School Pintar (SSP): Model PKM Unggulan Kelanjutusiaan Berbasis Literasi Digital dan Pemberdayaan Lansia di Jakarta Timur - Agustin, Dinni; Rosa, Tina; Patiroh, Yeti; Sari, Dewi Nawang; Widayati, Titik; Sari, Ramadhani Ulan (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2026)
The steadily increasing elderly population demands the strengthening of community-based empowerment programs, including digital literacy. This study aims to analyze the implementation and effectiveness of the Senior School Pintar (SSP) program in enhancing digital literacy and independence among the elderly in East Jakarta. The program was implemented for 25 elderly participants across 65 urban villages, totaling 1,625 participants, conducted over 6 months (12 learning sessions) from April to September 2025 using a hybrid learning approach. The evaluation design utilized a simple one-group pre-test and post-test method with skill observation instruments and satisfaction questionnaires. The results showed an increase in the digital capabilities of the elderly, including: WhatsApp usage increased from 35% to 85%, video call proficiency from 20% to 75%, access to health information from 25% to 80%, and digital self-confidence from 30% to 88%. A total of 92% of participants expressed satisfaction with the program. Furthermore, there was an improvement in the understanding of healthy lifestyles and social participation among the elderly. In conclusion, the SSP program has proven effective as a digital literacy-based empowerment model for the elderly and has the potential to be replicated at other community levels